GLI contributed to the regeneration of local plant species: The case for restoring biodiversity in Ethiopia - Mengistu, Dejene K; Terefe, Hailu; Nigir, Bogale; Tilahun, Abiyou (2025)
Ethiopia’s Green Legacy Initiative (GLI) aims to reverse land degradation, expand green cover, and restore biodiversity. Though criticized for favoring a few exotic species (Grevillea robusta, Vachellia deccurens, Pinus patula, and Cupressus lusitanica), our findings suggest these plantations effectively support native species regeneration in GLI sites. This underscores GLI’s potential in biodiversity restoration, climate resilience, environmental health, and socio-economic gains. However, challenges—open grazing, seedling loss, technical gaps, low community participation, and weak law enforcement—threaten sustainability. Urgent action is needed to address these issues and scale successes regionally.